Erosion Hazard Level in Jenelata Watershed, Gowa Regency, South Sulawesi, Indonesia Based on RUSLE Model - Abdul Akbar; Burhanuddin Rasyid; Rusnadi Padjung; Aminah Aminah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Erosion is the main problem that affects soil health related to agricultural activities, therefore this study aims to determine the level of erosion hazard in the Jenelata Sub Watershed. RUSLE is used to calculate erosion prediction using rainfall erosion information, soil erodibility value, topographic value and using maps for vegetation and conservation practices, so that erosion values are obtained for Buakkang, Bissoloro, Bontomanai, Jenebatu, Sapaya Village, Paranglompoa, Pattalikang, Tassese, Mangempeng, Paladigan, and Ronaloe. Each was divided into very low classes with land loss of less than 15 t/ha/year with a land area of 7812.38 ha. The low class was land loss of 15 to 60 t/ha/year with a land area of 3263.04 ha. The medium class was land loss of 60 to 180 t/ha/year with a land area of 694.76 ha. The high class was land loss of 180 to 480 t/ha/year with a land area of 3234.03 ha, and the very high class was land loss that is greater than 480 t/ha/year with a land area of 5272.67 ha. This study showed high and very high erosion with a land area of 3234.03 ha and 5272.67 ha and very low erosion with a land area of 7812.38 ha.